The Impact of Social Media Use on Adolescent Mental Health: A Scoping Review - Diana, Rini Nur; Kusuma, Nur Intan (Women, Midwives and Midwifery, 2025)
Background: Adolescents are an age group highly exposed to social media in their daily lives. The high intensity of social media use has raised concerns about its negative impact on adolescent mental health. Purpose: This review aims to map the scientific evidence related to the impact of social media on mental health in adolescents. Methods: Using the Arksey and O'Malley scoping review framework, this study followed five key stages: formulating the research question, identifying relevant literature, selecting appropriate studies, organizing the data, and reporting the findings. Articles were searched through the PubMed database and the Google Scholar search engine, covering publication years 2021–2025. A total of 80 articles were screened using the PRISMA flowchart and critical appraisal, following the Joanna Briggs Institute (JBI) guidelines, resulting in eight articles meeting the inclusion criteria. Results: Three main themes emerged: intensity of social media use, disturbed sleep quality, and mental health disorders such as stress, anxiety, and depression. Most adolescents use social media for more than three hours per day, with TikTok and WhatsApp being the dominant platforms. High usage correlates with increased sleep disturbances and the risk of depressive symptoms and stress. Conclusion: Social media has a significant impact on adolescent mental health. Digital literacy education and parental supervision are crucial to prevent these negative impacts.